Understanding Cognition, Oxytocin, and Pain in Elders (UCOPE): protocol for a double-blinded cross-over trial in chronic knee osteoarthritis pain - Yenisel Cruz-Almeida; Soamy Montesino-Goicolea; Pedro Valdes-Hernandez; Zhiguang Huo; Roland Staud; Natalie C. Ebner (Trials)
Abstract Background Osteoarthritis (OA) is the leading cause of disability among older adults with the knee being the most affected joint. Specifically, there is an urgent need to develop better analgesics for individuals with OA-related pain, since currently used analgesics frequently fail to provide adequate relief or must be discontinued owing to adverse effects. A promising treatment is the neuropeptide oxytocin (OT), which has been shown to play a role in endogenous analgesia with human and animal studies demonstrating anti-nociceptive effects. The primary aims of the study are to examine preliminary analgesic effects of a chronic OT intervention in community-dwelling older individuals with chronic knee osteoarthritis pain. Methods In this article, we describe the rationale and design of the Understanding Cognition, Oxytocin, and Pain in Elders (UCOPE) study, a double-blinded intervention in which 80 participants over 45 years of age with knee osteoarthritis pain will be recruited to participate in a cross-over trial of 4 weeks of intranasal oxytocin or placebo administration. Primary study outcomes include preliminary changes in pain intensity and interference as well as multi-modal assessment batteries including circulating biomarkers and neuroimaging measures. Self-reported and quantitative outcomes will be assessed at baseline, post-intervention periods, and up to a 6-month follow-up period. Discussion This study will establish preliminary effectiveness of a novel intervention in middle to older aged adults with knee osteoarthritis pain. Achievement of these aims will provide a rich platform for future intervention research targeting improvements in pain and disability among geriatric populations and will serve as a foundation for a fully powered trial to examine treatment efficacy and potential mechanisms of the proposed intervention. Trial registration ClinicalTrials.gov NCT03878589. Registered on March 18th, 2019.